Evaluating the Developed Model of Experimental Rhinitis in Laboratory Rats: Pre-Clinical Experimental Randomized Study - I. Ye. Berest; T. P. Tananakina; O. V. Teleshova; E. V. Burgelo; R. A. Parinov; A. V. Koretsky (Кубанский научный медицинский вестник, 2023)
Background. Among the damaging factors affecting the mucociliary system of the nasal cavity, surgical wound is of particular relevance in the practice of an otorhinolaryngologist. The clinical assessment of regeneration of the mucociliary system is associated with certain difﬁ culties, since the intravital morphological examination of the nasal mucosa in patients is traumatic. Therefore, the development of animal models of experimental rhinitis is considered to be highly relevant in order to study the dynamics of mucociliary pathomorphological changes and assess the epithelium regeneration.Objectives. To evaluate the developed model of experimental rhinitis in laboratory rats by studying clinical, morphological and biochemical changes in the inﬂ ammatory process.Methods. The experimental rhinitis model was developed and tested on 60 mature male Wistar rats. All animals were randomized into two groups: experimental group #1 (n = 30) — rats in which experimental rhinitis modeling was performed and group #2 (n = 30) — control, intact animals. In the course of the experiment, the authors examined the content of CRP in blood, evaluated the differential blood cell count, and studied a morphology of the nasal septum mucosa in 2, 5, 10 days after the injury to assess the dynamics of the inﬂ ammatory process in rats of both groups. Statistical analysis of the study results was carried out by means of Statistica 8.0 (StatSoft Inc., USA).Results. After injury, the rats from group #1 developed acute rhinitis, which was clinically manifested by the release of mucous or mucopurulent secretion from the nostrils, sneezing and scratching the nose. An increase in CRP, band and segmented neutrophils, and a decrease in lymphocytes were observed in blood of the rats from group #1 in comparison with the control group. Microscopic analysis of changes in the nasal septum mucosa showed that the acute phase of exudative inﬂ ammation developed on the second day: vascular congestion, edema, neutrophilic inﬂ ammatory inﬁ ltration of the submucosal membrane were observed against the background of foci of epithelial necrosis. The proportion of lymphocytes and macrophages in the inﬂ ammatory inﬁ ltrate increased by the ﬁ fth day, initial signs of restoration of epithelial tissue — the formation of an undifferentiated regenerating epithelium — appeared by the tenth day.Conclusion. The results of the study show that an adequate experimental model of acute rhinitis in laboratory animals have been obtained. An acute inﬂ ammatory process is characterized by clinical manifestations and changes in blood parameters. Particular destructive and reparative-proliferative changes develop in the mucous membrane of the nasal septum of experimental animals as a result of a surgical wound.